2018
DOI: 10.1186/s40545-018-0154-x
|View full text |Cite
|
Sign up to set email alerts
|

Prescription drug coverage in Canada: a review of the economic, policy and political considerations for universal pharmacare

Abstract: BackgroundCanadians have long been proud of their universal health insurance system, which publicly funds the cost of physician visits and hospitalizations at the point of care. Prescription drugs however, have been subject to a patchwork of public and private coverage which is frequently inefficient and creates access barriers to necessary medicine for many Canadians.MethodsA narrative review was undertaken to understand the important economic, policy and political considerations regarding implementation of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 32 publications
0
53
0
Order By: Relevance
“…Our results lend support to calls for a national pharmacare program, which could potentially reduce prevalence of cost-related nonadherence by providing universal prescription insurance. [35][36][37] However, as suggested by our finding that 564 (6.3%) of the 8943 insured adults in our sample reported cost-related nonadherence, the extent to which insurance mitigates cost-related nonadherence depends on the out-of-pocket expenditures required. The dose-response relation between food insecurity and cost-related nonadherence that we found suggests the need for greater reductioneven exemption -of out-of-pocket drug expenses among those experiencing more severe food insecurity.…”
Section: Openmentioning
confidence: 54%
“…Our results lend support to calls for a national pharmacare program, which could potentially reduce prevalence of cost-related nonadherence by providing universal prescription insurance. [35][36][37] However, as suggested by our finding that 564 (6.3%) of the 8943 insured adults in our sample reported cost-related nonadherence, the extent to which insurance mitigates cost-related nonadherence depends on the out-of-pocket expenditures required. The dose-response relation between food insecurity and cost-related nonadherence that we found suggests the need for greater reductioneven exemption -of out-of-pocket drug expenses among those experiencing more severe food insecurity.…”
Section: Openmentioning
confidence: 54%
“…For example, in Canada, the majority of dental care services are provided by private clinics and funded by private insurance or out-of-pocket payments [62,63] and are therefore poorly accessible to lowincome and socially excluded people. Moreover, Canada is the only socioeconomically developed country that provides universal coverage for health care services but not for prescription drugs [62,64]. All of this contributes further to a high economic and comorbidity burden and health inequities for low-income people without private insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Several empirical studies have demonstrated the financial hardships suffered by Canadians because of the uninsured costs of pharmaceutical drugs. 11,16,17 Even with brief periods of public attention in the past, the topic of pharmacare has remained relatively untouched by Canadian policy-makers because of a lack of electoral incentives and general concern over costs to be incurred by government 18,19 -despite robust cost proposals by Morgan and colleagues, 20,21 and Wolfson and Morgan. 22 Recently, however, pharmacare has become a central topic of public discussion and political discourse, which is demonstrated by its inclusion in the platforms of major political parties for the recent federal election and the establishment of the federal government's Advisory Council on the Implementation of National Pharmacare.…”
Section: Introductionmentioning
confidence: 99%